Mandatory Wills as Protection of Inheritance Rights to Heirs Who Change Religions : (Dimensions of Religious Education in the Family) - Nuryadin Nuryadin; A. Syaifullah; Ahmad Riyadh Maulidi (Scholar Center, 2022)
Obligatory will, occurs due to legal actions by changing religions other than Islam which causes no inheritance. But still get a chance with the provisions of the obligatory will. In this study, there was a legal conflict, namely Law no. 01 of 1974, Article 42, reads that a legitimate child is a child born in or as a result of a legal marriage. This does not see, due to other legal actions when the child is an adult by changing religions other than Islam. This is contrary to Faridh Law (law of Fiqh Inheritance), Al Qur'an Surah An Nisa verses 7 to 12. Also, Child Protection Law No. 23 of 2000, Article 42; Paragraph (2) reads that every child can make his choice if the child is wise and responsible and fulfills the requirements and procedures in accordance with the provisions of the religion he embraces and the provisions of the applicable laws. To provide a solution between these legal conflicts, a court decision regarding the obligatory will appeared, in court decision Number 204/Pdt.G/2007/Pa.Jr, which was confirmed by decision Number 263/Pdt.G2007/PTA.Sby and the decision of the Religious court Tondano Number 13Pdt/.G/2006/PA.Tdo, which was corrected by Decision Number 01/Pdt.G/2007/PTA.Mdo. This article will be examined using normative research methods, namely research that aims to obtain legal materials obtained through literature studies that are considered relevant to the subject matter. The results of this study are that boys and girls of different religions will still get an inheritance, but differences in the division of inheritance on the male side, the role of religious education functions to provide reinforcement in the values of Sakinah Mawaddah and Warahmah in the family, so religious education is needed. The conclusion of this study is that the obligatory will can provide strengthening of family values.